Medium. The complete first season [videorecording (DVD)] - Arquette, Patricia, 1968-; Weber, Jake, 1964-; Sandoval, Miguel, 1951-; Lark, Maria, 1997-; DuBois, Allison (Paramount Pictures, 2006)
Inspired by the life story of Allison DuBois, a woman who can communicate with the dead, but for most of her life she viewed this gift as a curse. Allison finally submits to her calling when she realizes she can do more good as a medium than as a lawyer.